Immuno‐Oncology Biomarkers for Gastric and Gastroesophageal Junction Adenocarcinoma: Why PD‐L1 Testing May Not Be Enough. (27th April 2018) - Weinberg, Benjamin A.; Xiu, Joanne; Hwang, Jimmy J.; Shields, Anthony F.; Salem, Mohamed E.; Marshall, John L.
Abstract: Purpose: The treatment of patients with advanced gastric and gastroesophageal junction (G/GEJ) adenocarcinomas has been transformed by the U.S. Food and Drug Administration approval of pembrolizumab. Tumor and adjacent tissue must stain positively for the programmed cell death ligand 1 (PD‐L1) protein by companion diagnostic testing. However, some patients with PD‐L1‐negative tumors also benefit from pembrolizumab. High microsatellite instability (MSI) and tumor mutational load (TML) are positive predictive biomarkers for immune checkpoint inhibition (ICI) in other tumors. We sought to identify more patients who could benefit from ICI using alternative PD‐L1 thresholds, MSI, and TML. Methods: Tumor specimens underwent next‐generation sequencing (NGS) and PD‐L1 testing using immunohistochemistry. NGS was used to determine TML and MSI. Results: We profiled 581 G/GEJ adenocarcinoma specimens. PD‐L1 staining was scored for intensity (0, none; 1+, weak; 2+, moderate; 3+, strong). Using 2+ staining at a 5% threshold, 9.3% of tumors were PD‐L1 positive, and using 1+ staining at 1%, 16.2% were PD‐L1 positive. 6.9% of tumors had high MSI. High TML (≥17 mutations per megabase) was seen in 6.9%, and medium TML (≥7) was seen in 56.5% of tumors. Thirty (5.2%) PD‐L1‐negative tumors at the 1+, 1% threshold had high TML or high MSI. Primary tumors had higher rates of high TML (8.8% vs. 3.9%; p = .0377) and high MSI (8.5% vs. 3.9%; p = .0471) than metastases. Conclusion: PD‐L1 testing alone fails to detect patients who may benefit from ICI. Lower PD‐L1 thresholds and TML testing should be considered in future clinical trials. Implications for Practice: Pembrolizumab is approved by the U.S. Food and Drug Administration for patients with refractory gastric and gastroesophageal cancers if the tumor and adjacent tissue stain positively for the programmed cell death ligand 1 (PD‐L1) protein by companion diagnostic testing. Tumor mutational load, microsatellite instability (MSI), and alternative PD‐L1 testing thresholds may serve as predictive biomarkers for response to immune checkpoint inhibition, and standard PD‐L1 testing will not identify all patients who may benefit from this therapy. Abstract : Although PD‐L1 is an important predictive biomarker for response to immune checkpoint inhibition in gastric and gastroesophageal junction adenocarcinoma, high microsatellite instability (MSI), mismatch repair deficient, and high tumor mutational load (TML) have a potential role as positive predictive biomarkers for immune checkpoint inhibition in other tumor types. This study aimed to identify more patients with gastric and gastroesophageal junction adenocarcinoma that have these positive biomarkers and to delineate the overlap between PD‐L1, MSI, and TML.